The myth of cyber-security. (Economist, 2017)
The article focuses on the rising risk of cyber-security like cyber thieves stealing from the Bank of Bangladesh, takeover of Yahoo by internet company Verizon and Russian hacker's interference with the American Presidential elections. It tells about the use internet of things (IoT) by every computer and technology making it difficult for hackers than the hacking of computers. It discusses the use of malware in technologies making them susceptible to hacking and other attacks.